Bank credit and productivity: Evidence from Mexican firms - Mario Villalpando Benítez (Banco de México, 2015)
Based on a survey of Mexican firms, this paper provides evidence of the positive effect of bank credit on firms' productivity. This effect is larger for those firms with access to bank credit and investment opportunities than for firms that only have either investment perspectives or bank credit. The potential problem of endogeneity in the empirical estimates is addressed by using instruments - collateral and expenses on energy and telecommunications - for the main explanatory variables. The relevant parameters indicating a positive effect of bank credit to productivity are consistent between estimation techniques.
Keywords: D22; D24; 330; bank credit; labor productivity